Optimization of Energy Systems in a Distribution Micro grid: An Application of the Particle Swarm Optimization - Waleed Khalid Al-Azzawi; Ahmed Kateb Jumaah Al-Nussairi; Hussein Riyadh Taresh; Zainab R. Abdulsada; Kadhum Al-Majdi; Ali H. A; Julayeva Zhazira (Majlesi Journal of Electrical Engineering)
This article proposes a method for optimizing the energy systems in a distribution micro-grid using particle swarm optimization. The method considers the optimal production planning of simultaneous production systems and takes into account the loss of electric energy transmission resulting from the concurrent production systems to the grid bus. The article establishes the correlation between the development of optimal load distribution methodology systems and the supply of electrical or thermal load. The advantages of the proposed algorithm have been demonstrated through numerical studies and comparisons, which showed a reduction in operational expenses, carbon dioxide emissions, and fuel consumption during both summer and winter seasons. The proposed method is an effective way of providing the required electrical energy of the sub-grid with minimal compliance requirements. The implementation of the proposed method during a single day and night in the summer season results in significant reductions of 17.5%, 13%, and 1% in operational expenses, carbon dioxide emissions, and fuel consumption, respectively. In the winter season, the pre-charge method also results in reductions of 10%, 7%, and 2% in operating cost, carbon dioxide emissions, and fuel consumption, respectively.